Cytological sampling of the uterine cervix: knowledge and perceptions of women who go through the exam - Simone Wünsch; Stefanie Griebeler Oliveira; Raquel Pötter Garcia; Izaura Bica Domingues (Universidade Federal de Santa Maria, 2011)
This study aimed to investigate the knowledge and the perceptions of women regarding uterine cervix cytological sampling. A qualitative research, characterized as exploratory and descriptive was conducted in a countryside city in the South of Brazil. Such study was carried out with women who looked for medical assistance to go through the test, in three Family Health Units. Saturation criterion was considered, regarding each FHU, as for definition of the number of participants. Data collection was accomplished through interviews, which were followed by thematic analysis. The women present knowledge about the aim of the exam. Besides, feelings such as shame and embarrassment emerged, which are culturally built and established as barriers for the test